Physico-chemical Water Quality Parameters of Damanganga Estuary, Daman - Dubey, Monika; Bindra, Piyush (Journal of Soil Salinity and Water Quality, 2023)
The present study was carried out to statistical approach on water quality of Damanganga estuary, Daman. For this study water samples were collected from Damanganga estuary during December to May 2021. The range of water quality parameters were observed such as water temperature (27.83±0.72) 0C, pH (8.35±0.05), salinity (10.83±2.39) part per thousand (ppt), dissolved oxygen (7.80±0.46) mg l-1, chloride (5157.16±433.47) mg l-1, total hardness (2633.33±147.57) mg l-1 calcium hardness (1322.71±107.80) mg l-1, magnesium hardness (1310.56±108.27) mg l-1 and Total alkalinity (115±3.86) mg l-1 were analyzed. Study revealed that chloride, total hardness, calcium hardness, and magnesium hardness were outside the range (WHO (1993), CPCB (2007), BIS (2012), EPA (2009) and water pollution index (WPI) is III category (1.202) indicated Damanganga estuary was moderately polluted.